Kinerja Website Pemerintah Daerah Kabupaten Sukabumi - Rerung, Rintho Rante; Fauzan, Muhammad; Safarudin, Muhamad Sigid (Yayasan Petra Harapan Bangsa, 2020)
This research aims to evaluate the performance of 10 websites managed by the Sukabumi Regency Government. Currently, information technology has been able to create a revolution in various sectors, including the government sector. One such revolution is the digitization of information. The digitization of information in the government sector is to create good governance. The digitization of information is considered very massive. Website adoption continues to increase in the government sector. One of them is in the Regional Government of Sukabumi Regency. This website performance evaluation is intended to provide recommendations for improvements to the manager if the web site's performance is considered poor. Based on the online search results found ten websites managed by the Regional Government of Sukabumi Regency. The website performance evaluation will be carried out using the GTmetrix tool. Website adoption continues to increase in the government sector. One of them is in the Regional Government of Sukabumi Regency. This website performance evaluation is intended to provide recommendations for improvements to the manager if the web site's performance is considered Poor. Based on the online search results found ten websites managed by the Regional Government of Sukabumi Regency. The website performance evaluation will be carried out using the GTmetrix tool. Based on the evaluation results, the performance of the website managed by the Regional Government of Sukabumi Regency using the YSlow Score is considered to be Quite Good, but the performance of the website using Page Speed Score is considered to be Poor. Therefore, it is necessary to improve the website's performance. One of the recommendations that has become a priority for improvement is to optimize images because it has become Priority Issues on ten websites managed by the Sukabumi Regency Government.Riset ini bertujuan untuk melakukan evaluasi kinerja terhadap 10 website yang dikelola oleh Pemerintah Kabupaten Sukabumi. Saat ini teknologi informasi telah mampu menciptakan revolusi di berbagai sektor, tidak terkecuali sektor pemerintahan. Salah satu revolusi tersebut adalah digitalisasi informasi. Digitalisasi informasi pada sektor pemerintahan adalah untuk mewujudkan tata kelola pemerintahan yang baik. Digitalisasi informasi dinilai sangat masif dilakukan. Adopsi website terus meningkat di sektor pemerintahan. Salah satunya adalah di Pemerintah Daerah Kabupaten Sukabumi. Evaluasi kinerja website ini dimaksudkan untuk memberikan rekomendasi perbaikan kepada pengelola jika kinerja website dinilai buruk. Dari hasil penelusuran secara daring ditemukan 10 website yang dikelola oleh Pemerintah Daerah Kabupaten Sukabumi. Evaluasi kinerja website tersebut akan dilakukan menggunakan alat bantu GTmetrix. Berdasarkan hasil evaluasi, diketahui bahwa kinerja website yang dikelola oleh Pemerintah Daerah Kabupaten Sukabumi dinilai Cukup Baik berdasarkan YSlow Score, namun dinilai Buruk berdasarkan Page Speed Score. Oleh karena itu, perlu perbaikan terhadap website. Salah satu rekomendasi yang menjadi prioritas perbaikan adalah to optimize images dikarenakan hal tersebut menjadi Priority Issues pada 10 website yang dikelola oleh Pemerintah Kabupaten Sukabumi.